Impact of water stress and nutrition on Vitis vinifera cv. ‘Albariño’: Soil-plant water relationships, cumulative effects and productivity - Martínez, Emma M.; Rey, Benjamin J.; Fandiño, María; Cancela, Javier J. (Spanish Journal of Agricultural Research, 2016)
The objective of the present study is to apply different systems of fertigation (rainfed, R; surface drip irrigation, DI, and subsurface drip irrigation, SDI) in Vitis vinifera (L.) cv. ‘Albariño’ to evaluate the cumulative effect of water stress (water stress integral) on yield parameters and to establish the relationship between indices and production. The study was conducted over four years (2010-2013) in a commercial vineyard (Galicia, NW Spain). The volumetric soil water content (θ) (with TDR) and predawn (ψp), midday (ψm) and stem (ψstem) leaf-water potential were determined with a water activity meter during the growing stages (flowering-harvest) from 2010-2013. The number of clusters, their weight and yield/vine were determined at harvest. Must composition was studied to evaluate nutrition treatments. Ψp is presented as the best indicator of the water status of the plant, and the sole use of θ is not recommended as a reference. The soil-plant water status variables were strongly correlated, especially between foliar variables (0.91<R2<0.98), with θ presenting the lowest reliability (0.28<R2<0.81). SDI was the treatment with the highest hydric comfort and greater yield/vine (6.1 kg) and weight per cluster (95.0 g), but lower elements concentration in must. The water stress integral showed that the veraison and harvest stages were very sensitive to water stress in vines. Linear relationships were established between Sψp and W (R2=0.65) and Y (R2=0.56) at veraison. The water stress integral is presented as a useful working tool for vine growers because it allows the prediction of future yield at early phenological states.